Men’s self-presentation attractiveness in the interview at assessment of sex-typed, crosssex-typed, undifferentiated and androgyny women and men - Korzeń, Renata; Matera, Urszula (Studia Psychologica: Theoria et praxis, 2006)
The participants of research were 160 women and 140 men, students of high schools. First participants filled in Polish version Bem Sex Role Inventory, then they chose physical attractive or unattractive man’s photograph and they read written form of self-presentation (in modest or boastful version). Finally they assessed the following target’s features: beauty, modesty, likeability and intelligence and they decided on employment. Modest self-presenter was often employed than boastful one. Physical attractive self-presenter was often employed than unattractive one. Women and men more liked modest self-presenter than boastful one. Unattractive and boastful man was assessed as least intelligent but only in men’s opinion. Besides androgyny women most liked self-presenter.